Application of Business Intelligence to support decision making in determining competent laws in the culinary sector in Deli Serdang Regency using the decision tree algorithm. - Muhammad Irsyad; Darmeli Nasution (Yayasan Sinergi Multidimensi Kreatif, 2025)
This study examines the application of Business Intelligence (BI) in identifying high-potential culinary Small and Medium Enterprises in Deli Serdang Regency. By using the Decision Tree algorithm, a prediction model is built based on historical sales data, business characteristics, and business environment factors. The results of the model evaluation show that Decision Tree is able to classify competent Small and Medium Enterprises. Key factors that influence the success of Small and Medium Enterprises, such as product quality, marketing strategy, and access to financing, were successfully identified through decision tree analysis. This study concludes that the application of BI with the Decision Tree algorithm can be an effective tool for stakeholders in supporting the development of Small and Medium Culinary Enterprises in Deli Serdang Regency